Dielectric instabilities and phase transitions in pseudospin-electron model of HTSC system - Stasyuk, I.V. (Физика низких температур, 1996)
The possible dielectric instabilities and phase transitions in high-Tc superconductors are analyzed within the pseudospin-electron model involving Hubbard type electron correlations as well as their interaction with local an-harmonic vibrational modes. The calculation of the dynamic dielectric susceptibility χ(ω, q) is performed in the generalized random phase approximation. The instabilities with respect to the polarization and/or charge fluctuations are obtained from the temperature dependences of χ(ω, q). The behavior of low-frequency modes in the vicinity of these instabilities is investigated. The case of the infinity narrow electron band is considered in details.